ENERGY EFFICIENCY OF INDUSTRIAL CONCENTRATORS WITH EJECTOR THERMOCOMPRESSION - Gjerasimovski, Aleksandar; Gjerasimovska, Nataša; Šarevski, Vasko (University Ss. Cyril and Methodius in Skopje, 2023)
Research on the energy characteristics of systems with ejector thermocompression applied in industrial concentrators is presented in this paper. Ejector thermocompression achieves a significant increase in energy efficiency. The heat pump cycle in ejectors is realized through the compression of a portion of the waste steam from the solution being concentrated, which, together with motive steam from a boiler or another heat generator, is used as the driving steam for the concentration process. Thermocompression realized with thermal energy can represent a sig-nificant advantage over mechanical thermocompression. A setup for the production of concentrated sodium hydroxide (NaOH) solution with two ejector thermocompressors is presented, as well as a polygeneration system with a gas engine – electricity generator, and an ejector thermocompression system. The proposed solutions have high energy efficiency. By implementing thermocompression systems in the production of concentrates, the energy production costs are sig-nificantly reduced, which positively affects the cost of the produced concentrate. The surplus of electrical energy, as well as steam not used in the thermocompression processes, is used to supply energy for the needs of consumers in the production facilities.
Keywords: industrial concentrators, NaOH solution, polygeneration thermal systems, energy efficiency, gas engine – electricity generator, thermocompression